LINKING DEFENSE INDUSTRIAL POLICY AND MONETARY STABILITY: THE DEFENSE EXPORT-LED STABILIZATION FRAMEWORK FOR INDONESIA - Haekal Hakim, Novky Asmoro; Novky Asmoro (Jurnal Penelitian Progresif, 2026)
Exchange-rate volatility remains a persistent challenge for developing economies, particularly during periods of global monetary tightening and geopolitical uncertainty. In Indonesia, external shocks have increased pressure on the Rupiah and highlighted the limitations of relying solely on conventional monetary instruments to maintain currency stability. This study examines the potential role of defense technology exports as a structural source of foreign exchange earnings capable of supporting long-term monetary resilience.Using a descriptive-analytical qualitative approach supported by macroeconomic indicators, defense-industrial data, official reports, and scenario-based projections, the study develops the Defense Export-Led Stabilization Framework to explain the relationship between defense industrial policy and exchange-rate stability. The analysis evaluates the export readiness of Indonesia's major defense enterprises and assesses their potential contribution to foreign exchange inflows, current-account improvement, and reserve accumulation.The findings indicate that Indonesia's defense industry possesses sufficient technological capability and export readiness to generate significant foreign exchange earnings. Under a moderate export-expansion scenario, annual defense export revenues are projected to reach approximately USD 1.9 billion. These inflows may contribute to strengthening external-sector performance, increasing foreign exchange liquidity, and enhancing market demand for the Rupiah through export-driven mechanisms.This study contributes to the literature by linking defense industrial policy and monetary stability within a unified analytical framework. The proposed Defense Export-Led Stabilization Framework offers a strategic perspective on how technology-intensive defense exports can support long-term economic resilience and monetary stability in developing economies.